1994
DOI: 10.1002/jlb.56.2.133
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the carbocyclic nucleoside analogue MDL 201,112 on inhibition of interferon-γ-induced priming of Lewis (LEW/N) rat macrophages for enhanced respiratory burst and MHC class II Ia+ antigen expression

Abstract: The effects of the carbocyclic nucleoside MDL 201,112 and the purine nucleoside adenosine on the interferon-gamma (IFN-gamma)-induced priming of macrophages (m phi s) for the respiratory burst and major histocompatibility class II (MHC class II) Ia+ antigen expression were compared. Priming of purified, peritoneal m phi s from Lewis (LEW/N) rats for 18 h with recombinant rat IFN-gamma (rRaIFN-gamma) in the presence of either adenosine (100 microM) or MDL 201,112 (10 microM) resulted in a fourfold decrease in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 56 publications
1
16
0
Order By: Relevance
“…In agreement with the pharmacological data that IB-MECA was more potent than CGS 21680, an agonist which elicits its cellular effects mainly by activating the cAMP-PKA pathway (Lupica et al, 1990), the cAMP-dependent protein kinase inhibitor KT5720 failed to reverse the inhibitory effect of adenosine on fMLP-induced monocyte respiratory burst (Broussas et al, 1999). The inhibitory effect of adenosine on human monocyte/macrophage respiratory burst was recapitulated using both mouse (Si et al, 1997) and rat (Edwards et al, 1994) peritoneal macrophages; however, there was no detailed analysis of the adenosine receptors involved in either study.…”
Section: Adenosine Inhibits Monocyte/macrophage Oxidative Burstsupporting
confidence: 75%
“…In agreement with the pharmacological data that IB-MECA was more potent than CGS 21680, an agonist which elicits its cellular effects mainly by activating the cAMP-PKA pathway (Lupica et al, 1990), the cAMP-dependent protein kinase inhibitor KT5720 failed to reverse the inhibitory effect of adenosine on fMLP-induced monocyte respiratory burst (Broussas et al, 1999). The inhibitory effect of adenosine on human monocyte/macrophage respiratory burst was recapitulated using both mouse (Si et al, 1997) and rat (Edwards et al, 1994) peritoneal macrophages; however, there was no detailed analysis of the adenosine receptors involved in either study.…”
Section: Adenosine Inhibits Monocyte/macrophage Oxidative Burstsupporting
confidence: 75%
“…It has emerged that monocytes/macrophages are key cellular targets for adenosinergic regulation of inflammation, together with leukocytes and endothelium (30, 32, 100,147,174,191,203,212,216,262). Adenosine receptor stimulation in lipopolysaccharide (LPS)-stimulated monocytes/macrophages reduces production of tumor necrosis factor-␣ (TNF-␣) (30, 203, 245), interleukin-12 (101), and macrophage inflammatory protein (MIP)-1a (270), limits induction of inducible NO synthase (iNOS) (300), and represses expression of the membrane protein major histocompatibility complex II (71,300). Adenosine also inhibits endothelial cytokine secretion and expression of adhesion molecules (30) and NF-b activation and signaling stimulated by TNF-␣ in myeloid, lymphocytic, and epithelial cells (191).…”
Section: Cardioprotection Through Modulation Of Inflammationmentioning
confidence: 99%
“…Several groups have reported that adenosine A 3 receptors, when occupied, diminish synthesis and release of cytokines, such as tumor necrosis factor ␣, that are thought to play a central role in the pathogenesis of RA (13)(14)(15)(16)39). Because A 3 receptors in rodents are insensitive to theophylline (17), our results are most consistent with the surprising finding that blockade of A 3 adenosine receptors does not contribute to the antiinflammatory effects of MTX in this model of arthritis.…”
Section: Montesinos Et Almentioning
confidence: 99%
“…Pharmacologic studies with the murine air pouch model of acute inflammatory disease demonstrate that MTX-mediated increases in exudate adenosine inhibit inflammation via interaction with an A 2 (probably A 2A ) receptor. Other pharmacologic studies have indicated that adenosine may also act at A 1 or A 3 receptors to inhibit inflammation (12)(13)(14)(15)(16).…”
mentioning
confidence: 99%